Social Studies Teachers' Efforts to Improve Critical Thinking Skills Through the Project Based Learning (PjBL) Model in Class VIII Students at SMP Negeri 10 Semarang - Hidayah, Maika Arifatul; Sasea, Sanita Carolina (Universitas Pahlawan Tuanku Tambusai, 2026)
Social studies learning in junior high school requires the development of students' critical thinking skills, but eighth-grade students of SMP Negeri 10 Semarang still show low activity and difficulty in in-depth analysis. This study aims to describe students' critical thinking skills and analyze the efforts of social studies teachers through the Project Based Learning (PjBL) model. This qualitative case study design research involved a population of social studies teachers, vice principals of curriculum, and eighth-grade students, with a purposive sample of one teacher, one vice principal, and five representative students. Instruments included semi-structured interviews, observation, and documentation; data analysis used the Miles and Huberman model with triangulation. The results showed that students' critical thinking skills were at a developing stage, encouraged by PjBL through problem identification, group discussions, and presentations, as well as teacher efforts such as visual media and limited facility management. PjBL was effective as a constructivist facilitation, although limited in generalization.